Skid resistance analysis in relation to temperature and surface Conditions: a case study of Kaliurang Road KM 8–9 - Salsabiilaa , Desfilia; Hadi, Muhamad Abdul (Teknisia, 2026)
The high number of traffic accidents in Yogyakarta requires a review of road surface conditions, especially in terms of skid resistance which is considered a safety indicator. This study analyzes the effect of surface temperature and road condition on skid resistance value on Kaliurang Road KM 8-9 using British Pendulum Test (BPT) tool. This is based on the viscoelasticity of asphalt, micro and macro texture and the effect of water layers. The results indicate that an increase in temperature decreases skid resistance values, or British Pendulum Number (BPN), in all conditions, with dry values ranging from 90 to 74 and wet conditions ranging from 58 to 43. All test points complied with TRRL standard (>65 BPN) under dry condition while only STA 8+000-8+200 segment complied with minimum limit (>55 BPN) under wet condition. The relationship between surface temperature and skid resistance values was determined using Pearson correlation and simple linear regression analyses. The analysis results indicated a significant negative correlation between temperature and skid resistance values and a decrease in BPN of 0.849 in a dry and 0.950 in a wet condition for each increase of 1 °C in temperature. The results of this study showed that temperature and the presence of water are proven to be significant factors that reduce the skid resistance so that pavement maintenance on Kaliurang Road KM 8-9 is needed to reduce the risk of accidents.